COHERENCE IN THESIS PROPOSAL WRITINGS OF UNDERGRADUATE STUDENTS - J.C. Setyo Karjono (JELLT (Journal of English Language and Language Teaching), 2020)
In academic writing such as a thesis proposal, a learner should consider several variables. Not only does a learner consider the language uses such as choice of words and syntactic forms at the sentence level, but beyond the sentence, a learner should also pay attention to the organization and unity of all the ideas and information into cohesive and coherent paragraphs. However, many students encounter great difficulties in writing their proposals especially the introduction part which deals with the organization of paragraphs. For this reason, the writer analyzed the undergraduate students’ competence in thesis proposal writings. The organization of the ideas and information becomes a necessary part of writing thesis proposal because of it into cohesive and coherent paragraphs. However, many students often get difficulties, especially in the introduction part. This article is the study of the proposal writings which covers the organization, the unity and coherence of paragraphs, and the syntactic form and word choice. The subjects of this research were the students of the English Language Education Program at a private university in Yogyakarta, Indonesia who were writing their theses as their final project. All data sources were from the undergraduate students' initial thesis writings especially the Introduction part proposed by the students. The samples of data were taken according to the proportional sampling referring to the research fields in which the students were interested: English Language Teaching 50%, Linguistics 30%, and Literature 20%.  The result of the analysis shows that: (a) Mostly the students’ proposals addressed well organization though using somewhat developed explanations, exemplifications, or details; (b) They also displayed unity and coherence, though the connection of ideas was occasionally obscured; Considering the organization, unity and coherence are the most appropriate variety for the undergraduate students’ writing; therefore, the study suggests that more exposure to the standard guidance or rubric of thesis writing will be helpful.